KAJIAN PEMUPUKAN KALIUM DENGAN APLIKASI JERAMI PADI TERHADAP PERTUMBUHAN DAN PRODUKSI PADI SAWAH PADALAHAN SAWAH BUKAANBARUDI KABUPATEN BUTON, SULAWESI TENGGARA - -, ASMIN1; -, LA KARIMUNA (Jurnal Agroteknos, 2014)
Productivity of paddy rice in paddy field in the newly openedland is generally very low due to the low levels of soil fertility and high content of iron that is toxic to plants. Fertilization and appropriate amelioration is needed to improve and increase the productivity of paddy rice. The purpose of this study was to analyze the effect of the combination of K fertilization and rice straw on growth and yield of paddy rice and economic  feasibility of the wetland new openings, and to obtain the proper dosage for hay substituting K fertilizers in paddy fields of new openings. This study was conducted on farmers' fields in the hamlet Aweli,Wakangka village; subdistrict Kapuntori, Buton, Southeast Sulawesi, which was performed from June 2012 to December 2012.The experiment was arranged in a randomized block design with eight treatments and three replications. The treatments were seven straw combinations with K fertilization rate based on the results of soil analysis (HCl extract 25%)  coupled with the control (the farmers’ method). The treatments were as follows: (1) 100 kg KCl without rice straw; (2) 75 kg KCl ha-1+ rice straw 2.5 t ha-1; (3) 50 kg KCl ha-1+ rice straw 5 t ha-1; (4) 25 kg KCl ha-1+ rice straw 7.5 t ha-1; (5) 0 kg KCl ha-1+ rice straw 10 t ha-1; (6) 75 kg KCl ha-1 + rice straw compost 1.0 t ha-1; (7) 75 kg KCl ha-1 + 1.0 t manure ha-1; and (8) 0 kg KCl ha-1 + 1.0 t manure ha-1 (Farmers’ method.The research results showed that the rice straw 2.5 t ha-1 reduced the need of KCl, from 100 kg ha-1 to 75 kg ha-1 and effectively increased grain yield. Provision of 10 t of rice straw can substitute potassium fertilizer application and the results obtained did not differ significantly with administration of 100 kg KCl ha-1, while effectively reducing the level of iron poisoning. Wetland management of technological innovation of new openings by using rice straw with Potassium fertilization increased the yield of paddy and increased the value of the RC ratio of 1.9 to 2.1-3.1, or the value of BC ratio increased to 2-12 times fold higher compared with the treatment of farmers’ method.The highest profits obtained in the application of 75 kg KCl fertilizer ha-1 in combination with rice straw 2.5 t ha-1was in the amount of Rp. 11.597 million ha-1, followed by potassium fertilization with 100 kg KCl ha-1 without straw, and treatment of 0 kg KCl + 10 t rice straw ha-1, Rp.9.951.000 ha-1 and Rp.9.645.000 ha-1, respectively.